Analisis Kasus Garuda Indonesia vs Rolls-Royce Sebagai Kajian Hukum Perdata Internasional - Johari, Abdullah Ahmad; Pratama, M. Andra; Hendriansyah, Nicholas Ferdy; Rizha Claudilla Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Civil relations are not limited to the national sphere, but can also transcend national borders. These relations have existed since ancient Greece and continue to develop today. These transnational relations can give rise to legal issues, such as whether the relationship truly falls within the scope of international relations, the laws that apply to the relationship, and how disputes are resolved using which legal system. The purpose of this study is to analyze the Garuda vs. Rolls Royce case, which is part of international civil relations, raising the question of how this case can be included in the scope of international civil law studies and how one of the international conventions governing transnational civil law principles, namely UNIDROIT, can be applied. This study uses a normative approach that compares national and transnational legal systems to provide perspective on the case and a case approach that clearly explains the Garuda vs. Rolls Royce case, starting from the chronology and analyzing the case from the perspective of international civil law principles The results of this study found that this case falls under the scope of international civil law, where international civil law principles such as UNIDROIT can be applied in order to make progressive legal changes in regulating international civil relations to ensure legal protection and certainty for legal subjects. The implications of this research can be a catalyst for progressive legal changes in regulating international civil relations to ensure legal protection and certainty for legal subjects.